Problem-Based Learning (PBL) Approach Using Psychological Tools to Enhance Students' Mathematical Creative Thinking Abilities - Kamila Alifya Khalda; Aan Hendrayana; Jaenudin Jaenudin (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
The purpose of this research is to examine whether the creative thinking abilities of students who receive the implementation of the Problem-Based Learning (PBL) approach using psychological tools are better than students who receive learning treatment with the PBL approach. Additionally, the study aims to determine the differences in students' mathematical creative thinking abilities when viewed in terms of their early mathematical abilities at Islamic Integrated Junior High School Al-Izzah for the academic year 2022/2023. The research method applied in this study is mixed-method research with a concurrent embedded design. The data obtained consist of posttest and pretest results, early mathematical ability tests, and interviews. This study employs analytical techniques such as descriptive statistics, and inferential statistics, followed by two-way ANOVA and Scheffe's post hoc test. The results show that the implementation of the Problem-Based Learning (PBL) approach using psychological tools has a positive impact on students' creative thinking abilities. Keywords: problem-based learning (PBL), psychological tools, creative thinking abilities, and early mathematical abilities.